HAMBATAN DAN DUKUNGAN PROGRAM PEMBERANTASAN PENYAKIT MALARIA DI DESA GEDUNG PEKUON KECAMATAN LENGKITI KABUPATEN OGAN KOMERING ULU SUMATERA SELATAN - , Aprioza Yenni ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Malaria is an endemic in many parts of Indonesia, including Ogan Komering Ulu regency district Lengkiti. Malaria eradication Program has been conducted since 1997. Currently the district OKU also obtained funding from the Global Fund for malaria control activities. But until today, there is no decrease in malaria endemic areas. This study was conducted to answer several problems, mainly: them 1. How social and cultural influences on malaria eradication program. 2. How the implementation of the eradication program malaria. 3. How environmental influences on the emergence of malaria. The purpose of this research is to look at the barriers and support in the implementation of malaria control programs. The research took place during the month of June to September 2012 at the village of Gedung Pekuon, district of Lengkiti. Using participatory observation and in-depth interviews with the interview. Researcher collected data methods and relating to the knowledge of society and the malaria eradication program. Data were collected and analyzed from overall informants, consisting of 14 key informants and 16 informants. The results showed that malaria eradication program has not been optimally implemented. It is caused by various factors. The factors related to the environment and people's livelihood, social mobility, behavioral prevention and treatment of malaria eradication program. Villages topography were largely in hilly area makes it suitable for growing crops pepper, coffee and rubber. The number of opening new land for crops has led to the high mobility of the population to come out into the village. The number of migrants entering and leaving the village resulted in transmission of malaria continue to occur because there are indeed those already suffering from malaria in the origin area. Knowledge and behavior of informants who are low on the prevention and treatment of malaria are not in line with their attitude problem towards the success of the program. In case of sufferer, health personnel and funding limitations become a bottleneck in the implementation of the program. Expected increase in knowledge and behavior continue to be pursued so they are aware of the dangers and consequences of malaria. This work is done by way of providing information on a regular basis to maximize existing community activities. Such as recitation or wiridan. There should also be an increase in the capacity of health workers in malaria eradication program so that program execution can be in accordance with existing policies planned